2012
DOI: 10.1002/ppul.22721
|View full text |Cite
|
Sign up to set email alerts
|

Fraction of exhaled nitric oxide (FeNO) norms in healthy North African children 5–16 years old

Abstract: Our FeNO norms enrich the global repository of FeNO norms the pediatrician can use to choose the most appropriate norms based on children's location or ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
8
2
Order By: Relevance
“…Although the influence of lung function has been described in few studies [22, 25], it was a significant predictor for Fe NO in the present study. In fact, for the included females, MEF 50 (%) and TGV (L) explained a slight but significant Fe NO variability.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Although the influence of lung function has been described in few studies [22, 25], it was a significant predictor for Fe NO in the present study. In fact, for the included females, MEF 50 (%) and TGV (L) explained a slight but significant Fe NO variability.…”
Section: Discussioncontrasting
confidence: 62%
“…Recently, the Fe NO of a large group of healthy Tunisian/Arab children was prospectively measured [25]. It was shown that the available published children Fe NO norms did not reliably predict Fe NO in this population [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Since the two groups were matched for the aforementioned parameters, this study’s main finding is not impacted. Moreover, since 21%, 35%, and 53% of Tunisian adolescents had overweight, low socioeconomic level and were qualified as active, 18,19 this study group composition (12%-20% were overweight, 25%-50% had low socioeconomic level, and 57%-60% were active) reflected this “healthy” adolescents population as they exist in the real society, increasing the external validity of this study. Since height is the most important influencing factor of children lung growth, 20 and since the fasters were taller than the non-fasters (Table 1), the spirometric data were standardized with respect to height by applying the local spirometric norms.…”
Section: Population and Methodsmentioning
confidence: 77%
“…However, reports on the relationship between FeNO levels and age compared subjects aged 35–44 years to those aged 64 years and older [18], or between subjects aged less than 60 years to those aged 60 years and older [19]: that is, each group covered a wide age range. Reports on children include a study finding no difference in FeNO level by age in children aged 5–16 years [20], and a study that demonstrated no correlation between FeNO level and age in a group of children aged 8–15 years [21], suggesting that it was highly unlikely that the 1-year difference in age was responsible for the difference in FeNO levels.…”
Section: Discussionmentioning
confidence: 99%